Medical and surgical management of Pasteurella canis infectious keratitis. (2017) - Shah, Ankit; Talati, Mansi; Mauger, Thomas
Abstract: Introduction: We describe a case of refractory Pasteurella Canis keratitis that initially failed antimicrobial treatment but was successfully treated with a conjunctival flap followed by a penetrating keratoplasty. Case discussion: A 70-year-old male had persistent corneal edema related to previous herpes zoster keratouveitis with visual acuity of 20/400. An endothelial keratoplasty was performed with improvement in vision to 20/25. Several months after this surgery the patient developed a corneal infiltrate and cultures grew Pasturella canis . The infection persisted despite topical treatment with broad spectrum fortified vancomycin, tobramycin and fluoroquinolones. A conjunctival flap combined with corneal cryotherapy was performed to help mitigate symptoms and to allow the ulcer to heal. A penetrating keratoplasty was done several months later. Discussion: The patient achieved pain relief immediately after the flap was placed. Medications were tapered off in the following few months after the procedure. A penetrating keratoplasty was performed 4 months later. The patient has remained almost entirely symptom free, and the graft remained clear one year after surgery. Conclusions: A keratitis caused by Pasteurella canis that is resistant to medical therapy can be treated successfully with a conjunctival flap and cryotherapy followed by a penetrating keratoplasty.